Identifikasi Coxiella brunetii Menggunakan Pengujian Polymerase Chain Reaction pada Kambing Di Kota Kupang - Annytha Ina Rohi Detha (JURNAL KAJIAN VETERINER, 2019)
Identification of Coxiella brunetii using polymerase chain reaction method in goats in Kupang area at Nusa Tenggara Timur had been done. Coxiella burnetii as causative of Q fever zoonosis in human and livestock and become public health problem. Q fever is considered an occupation hazard and caused epidemics in abattoir, scientific worker and livestock worker. This analysis using first Polymerase Chain Reaction and Nested Polymerase Chain Reaction as sets of primer to detect C. burneti. There are 40 sampel as the material to detect agent Q fever. The sample derived from one of the residential houses in Kupang. First and Nested PCR result to identification of Coxiella brunetii using PCR method showed that 40 samples did not contain the material genetic of C. burnetii in goats in Kupang Nusa Tenggara Timur.